Transcriptome and single-cell analysis reveal the contribution of immunosuppressive microenvironment for promoting glioblastoma progression - Ni, Lulu; Sun, Ping; Zhang, Sujuan; Qian, Bin; Chen, Xu; Xiong, Mengrui; Li, Bing (Frontiers in Immunology, 2023)
Background and Objectives GBM patients frequently exhibit severe local and systemic immunosuppression, limiting the possible efficacy of immunotherapy strategies. Through which immunosuppression is established in GBM tumors is the key to successful personalized immunotherapies. Methods We divided GBM patients into subtypes according to the expression characteristics of TME typing related signature matrix. WGCNA analysis was used to get co-expressed gene modules. The expression activity of hub genes retrieved from co-expressed modules was validated in two single-cell datasets. Then, cell- cell interaction was calculated. Results Four subtypes were identified in TCGA and CGGA RNA-seq datasets simultaneously, one of which was an immunosuppressive subtype rich in immunosuppressive factors, low in lymphocyte infiltration and IDH1 mutation. Three co-expressed gene modules related to immunosuppressive subtype were identified. These three modules are associated with inflammatory response, angiogenesis, hypoxia and carbon metabolism, respectively. The genes of inflammatory response were mainly related to myeloid cells, especially TAM, angiogenesis was related to blood vessels, hypoxia and glucose metabolism were related to tumor, TAM and blood vessels. Moreover, there was enhanced interaction between tumor cells and TAM. Discussion This research successfully found immunosuppressive subtype and the major cell types, signal pathways and molecules involved in the formation of immunosuppressive subtype and will provide new clues for the improvement of GBM personalized immunotherapy in the future.